About tarantula - possible uses in medicine - Diana Cîmpian,; Romeo Teodor Cristina (Medicamentul Veterinar, 2018)
In recent years, tarantulas have become increasingly popular in terrariums because they are easy to maintain, do not require much space and because of their beauty. Venom from spiders, snakes, fish, snails and scorpions contain an advanced pharmacopoeia of natural toxins that target membrane receptors and ion channels to produce shock, paralysis, pain or death. Tarantula venoms represent one of the largest collections of chemical compound combinations in the world. They have been developed selectively to ultimately generate some extremely powerful, selective bioactive structures that have undergone a natural optimization process through millions of years of natural selection. The study of various types of venom has become, in recent years, a priority for medical sciences and biology. In this sense, veterinarians are called to know the tarantula as beings, their way of life, feeding, breeding, as well as how to obtain, preserve, analyze and use. The work brings information about the life of tarantula, the way of contention and especially about how to harvest and store the venom from this species.